Structural and mechanical performance of adobe with the addition of high-density polyethylene fibres for the construction of low-rise buildings. (September 2022) - Dominguez-Santos, David; Alberto Moya Bravo, Julio
Abstract: Adobe bricks have been used in construction since ancient times, due to their low cost, good performance and the ease of assembly and elaboration of these elements in construction. However, the low ductility and resistance of adobe could harm the structural behaviour of buildings, especially taller buildings. The addition of additives, in the form of abundant high-density polyethylene (HDPE) fibres, could improve the mechanical properties from a seismic and structural point of view. These improved adobes could replace factory bricks, whose mechanical deficiencies are similar to adobe (stiffness and flexural strength), and they could reduce the high cost of buildings today. This work analyses and compares the performance and structural performance that these elements acquire in framed buildings, compared to traditional adobe, incorporating different percentages of high-density polyethylene fibres (HDPE) in low-rise buildings (of 2 and 4 storeys), which are very abundant in areas of high seismicity. For this, models of structural frames are analysed, adding adobe walls using the mechanical results carried out in a laboratory at the University of Talca (Chile). The addition of a small percentage (0.6% and 1.2%) of HDPE in the traditional adobe, improves the ductility and the structural performance of the frames.